مخاطر وتداعيات تداول العملات المشفرة على استقرار القطاع المالي 2021- خلال الفترة 2017: Risks and Repercussions of Cryptocurrency Deliberating on The Stability of The Financial Sector During the period 2017-2021 - عون الله سعاد; عامري رضوان (Journal of North African Economies, 2025)
This study aims to take note of some aspects of cryptocurrencies, by clarifying their concept and types, then reviewing their most important advantages and benefits, the components of their issuance system and the technology on which they are based, arriving at a statement of the risks associated with their use, as well as raising the challenges they pose to local and international financial regulatory authorities. After the technical analysis of the trading prices of the most important cryptocurrencies and the follow-up of their development during the period 2017-2021, the study concluded that their trading prices are highly volatile and may be affected by external factors such as financial and political events, and trading on the margins raises financial risks, although cryptocurrencies have several benefits. At the economic level and at the level of individuals in light of the distinctive features that it enjoys, but there are many risks and challenges it faces, which in total are considered a direct threat to the security and stability of the financial system, which calls for the regulatory authorities to regulate or prohibit them.